Comparison of Anti-Inflammatory Effects of Flavonoid-Rich Common and Tartary Buckwheat Sprout Extracts in Lipopolysaccharide-Stimulated RAW 264.7 and Peritoneal Macrophages. (27th August 2017) - Nam, Tae Gyu; Lim, Tae-Gyu; Lee, Bong Han; Lim, Sol; Kang, Hee; Eom, Seok Hyun; Yoo, Miyoung; Jang, Hae Won; Kim, Dae-Ok
Abstract : Buckwheat sprouts have been widely consumed all around world due to their great abundance of bioactive compounds. In this study, the anti-inflammatory effects of flavonoid-rich common buckwheat sprout (CBS) and tartary buckwheat sprout (TBS) extracts were evaluated in lipopolysaccharide- (LPS-) stimulated RAW 264.7 murine macrophages and primary peritoneal macrophages from male BALB/c mice. Based on the reversed-phase HPLC analysis, the major flavonoids in CBS were determined to be C -glycosylflavones (orientin, isoorientin, vitexin, and isovitexin), quercetin-3- O -robinobioside, and rutin, whereas TBS contained only high amounts of rutin. The TBS extract exhibited higher inhibitory activity as assessed by the production of proinflammatory mediators such as nitric oxide and cytokines including tumor necrosis factor- α, interleukin- (IL-) 6, and IL-12 in LPS-stimulated RAW 264.7 macrophages than CBS extract. In addition, TBS extract suppressed nuclear factor-kappa B activation by preventing inhibitor kappa B-alpha degradation and mitogen-activated protein kinase phosphorylation in LPS-stimulated RAW 264.7 macrophages. Moreover, the TBS extract markedly reduced LPS-induced cytokine production in peritoneal macrophages. Taken together, these findings suggest that TBS extract can be a potential source of anti-inflammatory agents that may influence macrophage-mediated inflammatory disorders.